2023
DOI: 10.3171/case2320
|View full text |Cite
|
Sign up to set email alerts
|

Ventral intermediate nucleus deep brain stimulation for treatment-resistant focal aware motor seizures: illustrative case

Abstract: BACKGROUND Resection of the seizure onset zone (SOZ) is considered the gold standard for treating refractory focal aware seizures (FASs). When resective surgery is unadvisable, deep brain stimulation (DBS) of the anterior nucleus of the thalamus (ANT; ANT-DBS) has been the procedure of choice. However, less than half of patients with FASs respond to ANT-DBS. The need for alternative targets to effectively treat FAS is thus evident. OBSERVATIONS The authors report the case of a 39-year-old woman presenting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…Thalamic specific nuclei DBS has some apparent advantages over ANT DBS. First, in accordance with our present (LGN DBS) and previous (Vim DBS) results, 18 it is somewhat more efficacious than ANT DBS. Second, unlike ANT DBS, which is performed bilaterally and requires higher amplitudes, 8 , 12 , 16 , 17 it is performed unilaterally and with lower amplitudes (< 3.0 V), 18 thus significantly reducing the costs of the procedure and increasing the battery life.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thalamic specific nuclei DBS has some apparent advantages over ANT DBS. First, in accordance with our present (LGN DBS) and previous (Vim DBS) results, 18 it is somewhat more efficacious than ANT DBS. Second, unlike ANT DBS, which is performed bilaterally and requires higher amplitudes, 8 , 12 , 16 , 17 it is performed unilaterally and with lower amplitudes (< 3.0 V), 18 thus significantly reducing the costs of the procedure and increasing the battery life.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Vilela-Filho et al 18 reported a new target for FAMSs, the Vim nucleus, which reduced seizure frequency by 88%. Encouraged by these results, we hypothesized that the stimulation of different thalamic specific nuclei can modulate the abnormal electrical activity of the SOZ located in their respective cortical projection areas and thus started an open clinical trial to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is unclear whether the lesion was correctly located in the FF H, as CT and MRI were inconclusive in confirming the lesion site. It is possible that the lesion extended to the thalamus, such as the centromedian and ventrolateral nuclei, or that it also involved the cerebellothalamic tract, which has been reported to be effective for epilepsy, possibly due to lesion encroachment on the neighboring structures 16–18 . The target position of Jinnai et al is slightly lower and posterior to ours.…”
Section: Discussionmentioning
confidence: 47%